Pemberian Ganti Rugi kepada Konsumen Akibat Tindakan Anti Persaingan di Indonesia: Studi Putusan Komisi Pengawas Persaingan Usaha Nomor 25/KPPU-I/2009 tentang Penetapan Harga Fuel Surcharge - Muhammad, Ghifari Mardhi; Wiradiputra, Ditha (Institut Agama Islam Nasional Laa Roiba Bogor, 2026)
The determination of compensation due to anti-competitive actions should be given to consumers, because the Competition Law actually regulates the determination and payment of compensation to the injured party, namely the business actor or the injured community/consumers. However, in practice, the losses arising from the actions of business actors are only paid to the aggrieved business actors or the state treasury, where the state is not a direct aggrieved party, but consumers. Providing compensation to consumers due to anti-competitive actions is a relevant matter when applied with various mechanisms that can be taken by consumers.